(3odeM GdoedMs - (3SYO Hf Ydj Hf GdbGSe GdCfUGQj GdNRQLj GdMXjQj, CHh GdeYGdj (B( (3nOnqdGd GdocoJH (B)(3,J (B568 (3g` s
(3ChdgG (B:s
(3hHYO, HCYPH GdcdGe hbO LeYJ cJGHkG JaQb CHhGHkG s
(3BNQgG (B:s
(3hGdeYhd Ydi eSGeMI GdfGbO GdcGTa dbOQg, heUGdMI GdMGSO GdcGSa dHOQg s
(3GfXQ aj GdLRA GdChd GdQbe (B699 (3COHs
(3HBNQgG eWGdYI ehQNI aj TgQ QHjY GdBNQ SfI (B699(3g`s
(3hHChdgG Jedc eDQN SfI (B986(3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B86 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B212s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B5 - (3U (B170 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1560s
Keywords: (3GdCOHs